Development of strategy of the enterprise (Journal of Economic Research & Business Administration, 2016)
The algorithm of development of marketing strategies of enterprises of mechanical engineering. Highlighted the dependence of the logistics strategies of marketing strategies. We developed a mechanism of planning the logistics strategies of the enterprise, the algorithm of designing supply chains in the SCM system.